Validity of Buffer Solution Practical Guidelines Based on Green Chemistry and Chemoentrepreneurship for Senior High Schools : Validitas Panduan Praktikum larutan penyangga Berbasis Green Chemistry dan Chemoentrepreneurship untuk SMA/MA - Akrami, Fathatul; Andromeda, Andromeda (SEARCH: Science Education Research Journal, 2026)
Chemistry learning in schools still faces fundamental problems centered on student learning experiences. The demands of the National Curriculum that require students to have 21st-century skills and competencies have not been optimally realized in the learning process. Learning tools that guide students' learning process to develop soft skills are urgently needed. This study aims to test the validity of a buffer solution practicum guide based on green chemistry and chemoentrepreneurship for senior high schools (SMA/MA). The study used the Research and Development method with the Plomp model and Tessmer formative evaluation. Primary data were obtained through observation, interviews, and questionnaires, with lecturers as expert review validators and students in the one-to-one evaluation stage. Data were analyzed descriptively quantitatively and validity was determined using the Aiken's V index. The results showed that the product had reached prototype stage III with a valid category, with an Aiken's V value for the content aspect of 0.88, presentation aspect of 0.83, language aspect of 0.89, and appearance aspect of 0.86, and an average index of 0.86. Thus, this green chemistry and chemoentrepreneurship-based buffer solution practical guide is declared valid based on the results of the Aiken's V validity test.